Myogenic and cortical evoked potentials vary as a function of stimulus pulse geometry delivered in the subthalamic nucleus of Parkinson’s disease patients - Campbell, Brett A.; Favi Bocca, Leonardo; Tiefenbach, Jakov; Hogue, Olivia; Nagel, Sean J.; Rammo, Richard; Escobar Sanabria, David; Machado, Andre G.; Baker, Kenneth B. (Frontiers in Neurology, 2023)
The therapeutic efficacy of deep brain stimulation (DBS) of the subthalamic nucleus (STN) for Parkinson’s disease (PD) may be limited for some patients by the presence of stimulation-related side effects. Such effects are most often attributed to electrical current spread beyond the target region. Prior computational modeling studies have suggested that changing the degree of asymmetry of the individual phases of the biphasic, stimulus pulse may allow for more selective activation of neural elements in the target region. To the extent that different neural elements contribute to the therapeutic versus side-effect-inducing effects of DBS, such improved selectivity may provide a new parameter for optimizing DBS to increase the therapeutic window. We investigated the effect of six different pulse geometries on cortical and myogenic evoked potentials in eight patients with PD whose leads were temporarily externalized following STN DBS implant surgery. DBS-cortical evoked potentials were quantified using peak to peak measurements and wavelets and myogenic potentials were quantified using RMS. We found that the slope of the growth recruitment curves differed significantly as a function of pulse geometry for both the cortical- and myogenic responses. Notably, this effect was observed most frequently when stimulation was delivered using a monopolar, as opposed to a bipolar, configuration. Manipulating pulse geometry results in differential physiological effects at both the cortical and neuromuscular level. Exploiting these differences may help to expand DBS’ therapeutic window and support the potential for incorporating pulse geometry as an additional parameter for optimizing therapeutic benefit